Patriarchal investments: Marriage, dowry and economic change in rural Bangladesh - Sarah C. White (University of Bath, Centre for Development Studies (CDS), 2013)
Contemporary studies of marriage around the world note increased emphasis on 'choice' and 'conjugality'. In South Asia, such discussions have largely displaced an earlier focus on 'dowry' and its implications for the gendered vulnerability of women. This paper argues that considering together discourses of affinity and practices of dowry adds significantly to understanding of the complex inter-relations of social and economic change. Drawing on data from rural Bangladesh, it emphasises the materiality of marriage, its centrality to family advancement strategies and ongoing commitment to the governing idioms of masculine provision and protection. Against conventional views that dowry compensates for a perceived weakness in women's contribution, the paper argues that it functions to bolster men's. The contradictory faces of marriage as dowry or conjugality in South Asia may cast light on the broader political and economic transformations in which they arise.
Keywords: 330; Ehe; Soziale Lage; Frauen; Regionaler Strukturwandel; Ländlicher Raum; Bangladesch